Study on workability and strength of fresh and hardened concrete containing different percentage of chipboard waste - Nur Suhaida, Roslan (2012)
Nowadays people are paying more attention to the sustainability in construction field. So, the engineers are finding the ways to improve the quality of the concrete using recycle or waste product. One of the methods is to mix the chipboard with the concrete. In the research, a waste chipboard is already ayailable at Terang Bersih Landfill is used. The chipboard was replaced with coarse aggregate in the proportion of 10%, 20% and 30% by weight of cement. The laboratory tests include slump test, vebe test, compaction factor tests, compressive strength test and flexural strength test. All test methodology is referring to British Standard (BS). Concrete cubes of size 150 x 150 x 150 mm were casted for compressive strength and concrete beams of sizes 150 x 150 x 750 mm were casted for flexural strength test. Concrete with lowest percentage of chipboard replace in concrete has lower workability. For compressive strength, concrete with 10% chipboard content provides the highest strength compare to other percentages of chipboard but it still lower than the control set. For flexural strength test, concrete with 30% chipboard content shows the highest strength. The workability and compressive strength were decreased when more percentage of chipboard were added into concrete mix.